Longterm calcineurin inhibitor therapy and brain function in patients after liver transplantation. Issue 1 (21st December 2017) - Pflugrad, Henning; Schrader, Anna‐Kristina; Tryc, Anita Blanka; Ding, Xiaoqi; Lanfermann, Heinrich; Jäckel, Elmar; Schrem, Harald; Beneke, Jan; Barg‐Hock, Hannelore; Klempnauer, Jürgen; Weissenborn, Karin
Abstract : Calcineurin inhibitors (CNIs) frequently induce neurological complications early after orthotopic liver transplantation (OLT). We hypothesize that longterm CNI therapy after OLT causes dose‐dependent cognitive dysfunction and alteration of brain structure. In this study, 85 OLT patients (20 with CNI‐free, 35 with CNI low‐dose, and 30 with standard‐dose CNI immunosuppression) underwent psychometric testing and cerebral magnetic resonance imaging approximately 10 years after OLT to assess brain function and structural brain alterations. A total of 33 healthy patients adjusted for age, sex, and education served as controls. Patients receiving CNI showed a significantly worse visuospatial/constructional ability compared with controls ( P ≤ 0.04). Furthermore, patients on low‐dose CNI therapy had an overall impaired cognitive function compared with controls ( P = 0.01). The tacrolimus total dose and mean trough level were negatively correlated to cognitive function. CNI doses had been adjusted in 91% of the patients in the low‐dose and CNI‐free groups in the past due to CNI‐induced kidney damage. Patients treated with CNI showed significantly more white matter hyperintensities (WMH) than patients on CNI‐free immunosuppression and controls ( P < 0.05). Both the mean cyclosporine A and tacrolimus trough levels correlated significantly with WMH. In conclusion, longterm CNI therapy carries a risk of cognitive dysfunction especially in patients who already showed nephrotoxic side effects indicating an increased susceptibility of these patients against toxic CNI effects. This subgroup of patients might benefit from a change to CNI‐free immunosuppression. Liver Transplantation 24 56–66 2018 AASLD.